2010
DOI: 10.1021/nn901517u
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Optical Properties of Gold Nanoparticles Coated with a Charged Diblock Copolymer and an Uncharged Triblock Copolymer

Abstract: We demonstrate that the optical properties of gold nanoparticles can be used to detect and follow stimuli-induced changes in adsorbed macromolecules. Specifically, we investigate thermal response of anionic diblock and uncharged triblock copolymers based on poly(N-isopropylacrylamide) (PNIPAAM) blocks adsorbed onto gold nanoparticles and planar gold surfaces in a temperature range between 25 and 60 degrees C. By employing a palette of analytical probes, including UV-visible spectroscopy, dynamic light scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 38 publications
1
44
1
Order By: Relevance
“…In 2010 Volden et al showed that refractive index based sensing of changes in polymers can also be made on nanoparticles that are not located on a surface [45] . They used anionic diblock and uncharged triblock copolymers adsorbed onto gold nanoparticles and monitored the temperature response of the polymers.…”
Section: Polymer Swellingmentioning
confidence: 99%
“…In 2010 Volden et al showed that refractive index based sensing of changes in polymers can also be made on nanoparticles that are not located on a surface [45] . They used anionic diblock and uncharged triblock copolymers adsorbed onto gold nanoparticles and monitored the temperature response of the polymers.…”
Section: Polymer Swellingmentioning
confidence: 99%
“…These applications indicated a robust changing of the SERS signals depending on the distance between Au or Ag NPs and on Au flat surface. Others have reported the plasmon band changing of Au and Ag NPs coated on top of pH or solvent sensitive polymer brushes [12][13][14][15][16][17]. However, to best of our knowledge, optimization of the Raman signals resulted from changing of the distance between Au NPs on a temperature responsive poly[(2-methoxyethoxy)ethyl) methacrylate] [poly(MEO 2 -MA)] brush layer has never been reported so far.…”
Section: Introductionmentioning
confidence: 96%
“…Their properties can be changed by external stimuli such as temperature [1,2], light [3,4], electric and magnetic fields [5][6][7], ionic strength [8], pH [9] and chemicals [10,11]. Therefore, smart polymers are used in biotechnology, medicine and engineering, in such applications as drug delivery systems [12][13][14], chemical separation [15,16], sensors [17] and actuators [18,19]. The smart polymer that has been studied most extensively is poly(N-isopropylacrylamide) (PNIPAAm) [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%